2015
DOI: 10.1007/s00264-015-3067-1
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparative study shows no significant difference in postural stability between cruciate-retaining (CR) and cruciate-substituting (PS) total knee implant systems

Abstract: In case it is necessary to use a PS implant, no negative influence on postural stability is to be expected compared to a CR implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…To our best knowledge, similar studies do not exist in literature so far. Regarding the results of postural stability after total knee replacement and the influence of substituting or retaining the posterior cruciate ligament, it could be shown that, similar to the current study, patient regained the status of the nonoperated side independently from the surgical method [20]. Furthermore we could show that, in both groups, the overall postural stability of the operated side reached the level of the nonoperated side.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…To our best knowledge, similar studies do not exist in literature so far. Regarding the results of postural stability after total knee replacement and the influence of substituting or retaining the posterior cruciate ligament, it could be shown that, similar to the current study, patient regained the status of the nonoperated side independently from the surgical method [20]. Furthermore we could show that, in both groups, the overall postural stability of the operated side reached the level of the nonoperated side.…”
Section: Discussionsupporting
confidence: 87%
“…Despite superior clinical and functional results over TKA [4], unicompartmental knee resurfacing does not comprise better proprioception [19, 20] than TKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the success of knee arthroplasty using various endoprosthesis designs has been a topic of many examinations that are usually based on the use of subjective tests and the matching of patients with different types of endoprostheses [2,[11][12][13][14][15][16]. In our examination, an objective index of the gait pattern was used after knee arthroplasty in the same patient with, in one knee joint, an implanted endoprosthesis with sacrifice of the posterior cruciate ligament, and in the other, an endoprosthesis with a preserved posterior cruciate ligament.…”
Section: Discussionmentioning
confidence: 99%
“…Cruciate ligaments are indeed crucial for the stabilization and ROM of the knee in three planes. The current literature is still controversial regarding this topic [62], most reviews suggest that no significant differences in outcome exist between PCL retaining and PCL sacrificing techniques [63][64][65][66][67]. However, it is important to note that these studies were not conducted in highly active patients.…”
Section: Implant Specificationsmentioning
confidence: 99%